2014
DOI: 10.1155/2014/534382
|View full text |Cite
|
Sign up to set email alerts
|

Marginal and Internal Fit of Cobalt-Chromium Fixed Dental Prostheses Generated from Digital and Conventional Impressions

Abstract: Objectives. Digital impressions are increasingly used and have the potential to avoid the problem of inaccurate impressions. Only a few studies to verify the accuracy of digital impressions have been performed. The purpose of this study was to compare the marginal and internal fit of 3-unit tooth supported fixed dental prostheses (FDPs) fabricated from digital and conventional impressions. Methods. Ten FDPs were produced from digital impressions using the iTero system and 10 FDPs were produced using vinyl poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 23 publications
2
41
0
5
Order By: Relevance
“…Regarding the marginal fit, the results of the current study agree with the study of Svanborg et al, who found no significant difference for the absolute marginal gap of 3‐unit bridges fabricated using direct and indirect digitalisation techniques and pre‐defined marginal cement gap of 30 μm . Nevertheless, in the current study, the mean difference between the measured absolute marginal discrepancy and the pre‐defined marginal cement gap is higher than in the study of Svanborg et al . While the literature suggests the clinically acceptable marginal gap to vary from 50 to 200 μm, 120 μm is often referred to as the maximum clinically tolerable marginal cement gap .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the marginal fit, the results of the current study agree with the study of Svanborg et al, who found no significant difference for the absolute marginal gap of 3‐unit bridges fabricated using direct and indirect digitalisation techniques and pre‐defined marginal cement gap of 30 μm . Nevertheless, in the current study, the mean difference between the measured absolute marginal discrepancy and the pre‐defined marginal cement gap is higher than in the study of Svanborg et al . While the literature suggests the clinically acceptable marginal gap to vary from 50 to 200 μm, 120 μm is often referred to as the maximum clinically tolerable marginal cement gap .…”
Section: Discussionsupporting
confidence: 86%
“…Internal and marginal fit are two factors thought to be of high clinical importance for the long‐term survival and success of fixed dental prostheses (FDP) . Two different methods have been used for assessing the fit of reconstructions in vivo: (a) the replica method, which uses impression material to replicate the cement film, and (b) the triple scan technique, which uses digital technology to assess the cement gap by superimposing the preparation with both the internal and external surfaces of the reconstruction . However, these methods are mainly used in laboratory research as they are impractical in the clinic and very time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, no significant differences were seen between the investigated systems (iTero mean, 142 μm; Straumann CARES mean, 147 μm) [23]. Keul et al [12] investigated the marginal opening of 4-unit CoCr and zirconia frameworks also using the iTero and Straumann CARES system: CoCr frameworks from digital impressions showed significantly lower mean values for marginal fit than ones from conventional impressions (digital impression mean, 56.90 μm; conventional impression mean, 90.64 μm; p < 0.001).…”
Section: Discussionmentioning
confidence: 74%
“…A recent study reported that most of the newer intraoral scanners showed better precision than the older ones. 15 Optical impression systems will continue to improve, resulting in a more reliable complete arch impression for different treatment indications.…”
Section: Discussionmentioning
confidence: 99%